2011
DOI: 10.1128/mcb.00883-10
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin 1 Inhibits the GTPase-Activating Protein Function of ARHGAP21, Promoting Activation of RhoA following Angiotensin II Type 1A Receptor Stimulation

Abstract: Activation of the small GTPase RhoA following angiotensin II stimulation is known to result in actin reorganization and stress fiber formation. Full activation of RhoA, by angiotensin II, depends on the scaffolding protein ␤-arrestin 1, although the mechanism behind its involvement remains elusive. Here we uncover a novel partner and function for ␤-arrestin 1, namely, in binding to ARHGAP21 (also known as ARHGAP10), a known effector of RhoA activity, whose GTPase-activating protein (GAP) function it inhibits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 45 publications
6
65
1
Order By: Relevance
“…Activation of the angiotensin II type 1A receptor facilitated association of ␤Arr1 with the RhoGAP ARHGAP21, and consequent inhibition of the GTPase-activating proteins contributed to higher RhoA activity (16). Angiotensin II type 1A receptor was also shown to mediate RhoA activation through both ␤Arr1 and G q (13), as well as through JAK2-mediated phosphorylation of p115RhoGEF (17).…”
mentioning
confidence: 97%
“…Activation of the angiotensin II type 1A receptor facilitated association of ␤Arr1 with the RhoGAP ARHGAP21, and consequent inhibition of the GTPase-activating proteins contributed to higher RhoA activity (16). Angiotensin II type 1A receptor was also shown to mediate RhoA activation through both ␤Arr1 and G q (13), as well as through JAK2-mediated phosphorylation of p115RhoGEF (17).…”
mentioning
confidence: 97%
“…This pathway is dependent upon β-arrestin-1 but not β-arrestin-2 (11). Although the exact mechanisms of β-arrestin-1-mediated RhoA/ROCK signaling are still under investigation, it has been reported that β-arrestin-1 enhances angiotensin II-stimulated RhoA/ROCK signaling by inhibiting ArhGAP (12). The function of ArhGAP is to deactivate RhoA.…”
Section: Rhoa/rock Pathwaymentioning
confidence: 99%
“…In contrast to G protein-mediated signaling, a β-arrestin-biased agonist selectively activates bone formation. PTH-βarr (D-Trp 12 , Tyr 34 -βPTH ) is found to be a PTH receptor-biased agonist that activates β-arrestin-2 but not classic G protein signaling (24). PTH-βarr stimulated anabolic bone formation, and this effect was greatly decreased in β-arrestin-2-knockout mice (25).…”
Section: Pth-βarrmentioning
confidence: 99%
See 1 more Smart Citation
“…As the S1PR2 activates PTEN via a RhoAdependent pathway 33 , we tested several other GPCRs, known to stimulate RhoA-dependent signalling in HEK cells but that have not been reported so far to modulate PTEN activity in this system. The angiotensin type 1A receptor (AT1AR) has previously been shown to activate RhoA in HEK cells [34][35][36] . We first confirmed that the AT1AR can activate the Rho/ROCK pathway in HEK cells using an in vitro assay that measures ROCK activity.…”
Section: Establishment and Validation Of The Rluc-pten-yfp Biosensormentioning
confidence: 99%